TRANSFORMASI PELAYANAN PUBLIK BERBASIS AGILE GOVERNANCE: STUDI KASUS PADA MALL PELAYANAN PUBLIK DI KABUPATEN BANYUWANGI - Raycinta Septi Maharani Raycinta; Hesti Lia Ardista Hesti; Akbar Maulana Akbar (Interelasi Humaniora, 2026)
This study examines the transformation in public services through the application of agile governance principles with a case study at the Public Service Mall (MPP) in Banyuwangi, East Java. Agile governance, as a flexible management method, emphasizes the importance of intersectoral collaboration, agility in responding to community needs, and an iterative process for improvement. This study uses a descriptive qualitative approach based on a case study. Data collection was conducted through in-depth interviews with 15 key informants, participant observation, and a review of policy documents between 2019 and 2024. The research findings indicate that the Banyuwangi MPP has successfully implemented four main aspects of agile governance, which include: (1) agency adaptability by redesigning service processes based on citizen needs, (2) multi-stakeholder collaboration between local governments, state-owned enterprises, and the private sector, (3) digital service management that has successfully reduced the average document completion time by 68%, and (4) a direct feedback system that contributed to an increase in public satisfaction levels from 72% to 91% within a three-year implementation period. This case demonstrates that implementing agile governance can improve the effectiveness, efficiency, and quality of public services in the era of digital transformation. The results of this study provide valuable insights for developing a more agile, collaborative, and responsive public governance model to public needs.